2004
DOI: 10.1016/s0014-5793(04)00469-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of phosphatidylcholine biosynthesis under salt stress involves choline kinases in Arabidopsis thaliana

Abstract: Increasing evidence suggests a major role for phosphatidylcholine (PC) in plant stress adaptation. The present work investigated the regulation of choline, PC and interconnected phosphatidylethanolamine biosynthesis in Arabidopsis thaliana L. as a function of cold-and salt-or mannitol-mediated hyperosmotic stresses. While PC synthesis is accelerated in both salt-and cold-treated plants, the choline kinase (CK) and phosphocholine cytidylyltransferase genes are oppositely regulated with respect to these abiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 35 publications
2
57
0
Order By: Relevance
“…Furthermore, the expression of the PEAMT genes encoding a key enzyme of choline synthesis was induced in lpcat1 lpcat2-2 (Figure 9; see Supplemental Data Set 2 online). These results indicated that the metabolic response of increased de novo PC synthesis involves a series of highly orchestrated molecular steps (Tasseva et al, 2004;Keogh et al, 2009). The weak phenotype of reductions of 18:2 and 18:3 in the TAG of lpcat1 lpcat2-2 also supports the notion that Arabidopsis developing seeds have the capacity to channel 18:1 into PC for desaturation to 18:2 and 18:3 beyond the Lands cycle as well as metabolic plasticity for mobilizing PUFAs into TAG.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, the expression of the PEAMT genes encoding a key enzyme of choline synthesis was induced in lpcat1 lpcat2-2 (Figure 9; see Supplemental Data Set 2 online). These results indicated that the metabolic response of increased de novo PC synthesis involves a series of highly orchestrated molecular steps (Tasseva et al, 2004;Keogh et al, 2009). The weak phenotype of reductions of 18:2 and 18:3 in the TAG of lpcat1 lpcat2-2 also supports the notion that Arabidopsis developing seeds have the capacity to channel 18:1 into PC for desaturation to 18:2 and 18:3 beyond the Lands cycle as well as metabolic plasticity for mobilizing PUFAs into TAG.…”
Section: Discussionmentioning
confidence: 92%
“…The current prevalent view is that the pace-setting enzyme of the Kennedy pathway is not EK, but ECT (43,44). Furthermore overexpression of the EK in mammalian cells does not alter the steady-state levels of PE but only leads to an accumulation of glycerol-phosphoethanolamine (42).…”
Section: The Choline and Ethanolamine Kinasesmentioning
confidence: 99%
“…They also have two ethanolamine-specific kinases: EK1 with negligible CK activity and EK2 with higher affinity for ethanolamine than choline (42). Multiple CKs and a single EK have been identified in Caenorhabditis elegans and Arabidopsis thaliana (43,44), whereas several unicellular eukaryotes have only one member of this enzyme class, probably a dual specificity enzyme (7, 45, 46 and references therein).…”
Section: The Choline and Ethanolamine Kinasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Water-soluble metabolites were obtained from the aqueous supernatant and were fractionated by silica gel TLC developed with MetOH/0.5%NaCl/30%NH 4 OH 50/50/1 (Retention Factors Cho:0.07, Etn:0.16, P-Cho:0.32, P-Etn:0.57, CDP-Cho:0.71, Ser:0.78, and CDP-Etn:0.84) ( 35 ).…”
Section: Syntenic Regions Corresponding To the Genomic Context Of Phomentioning
confidence: 99%